Phenotypic Detection of Inducible Clindamycin Resistance in MRSA - Ahmed, Perinaz; Jaddoa, Nihad Taha Mohammed (Iraqi Journal of Science, 2026)
Staphylococcus aureus is a common pathogen associated with community and hospital-acquired infections; it can rapidly develop resistance to new antibiotics. The emergence of methicillin-resistant Staphylococcus aureus (MRSA) has severely limited treatment options, necessitating the judicious use of effective antibiotics such as clindamycin. However, routine susceptibility tests often fail to detect inducible clindamycin resistance (ICR), ultimately leading to treatment failures. This cross-sectional study was conducted from September 2023 to June 2024, and it aimed to identify and report the prevalence of ICR phenotypes among MRSA with the d-test. A total of 101 isolates were investigated, of which 85 were S. aureus and confirmed using PCR targeting the Sa442 fragment. They were identified as MRSA using the cefoxitin disk diffusion test. Among these, 32.94% showed ICR, of which 21.18% were D-phenotype and 11.76% were D+ phenotype. Constitutive Macrolide-lincosamide-streptogramin B cMLSB) resistance was observed in 32.94%, including hazy D zone (HD) (24.71%) and resistant (R) (8.24%) phenotypes. Sensitive, non-MLSB, and macrolide–streptogramin B  (MSB) phenotypes were detected in 27.06%, 3.53%, and 3.53%, respectively. Finally, D-test as part of routine antibiotic susceptibility is important for appropriate clindamycin use, mitigating treatment failures, and reducing the use of broad-spectrum antibiotics in Iraqi hospitals. Therefore, improving patient care in Iraq.